Advances in Characterization and Analysis of Expansive Soils and Rocks Proceedings of the 1st GeoMEast International Congress and Exhibition, Egypt 2017 on Sustainable Civil Infrastructures (Sustainable Civil Infrastructures,, 2018)
This volume includes a collection of technical papers covering two important research topics in geotechnical engineering: (1) the behavior and treatment of expansive soils, and (2) the characterization of rock properties. The twelve studies on expansive soils include investigations into novel stabilization techniques for expansive soils using different admixtures or mechanical consolidation techniques, as well as new experimental approaches to evaluate the behavior of expansive soils. They also include an evaluation of wetting boundary conditions on the volume change of expansive soils, as well as the role of hydrologic boundary conditions in arid climates. The four studies on rock properties include thermo-hydro-mechanical behavior of gypsum rock, role of rock strength in blastability, indirect methods to estimate rock strength, and variations in isotope distributions in Permian rocks. The two broad themes in this collection, as summarized above, are representative of local challenges facing geotechnical engineers in the Middle East, but their contributions can also be extended to other regions of the world. This volume is part of the proceedings of the 1st GeoMEast International Congress and Exhibition on Sustainable Civil Infrastructures, Egypt 2017.